Spectro-Spatial Unmixing in Optical Microspectroscopy for Thickness Determination of Layered Materials - Schwarz, Julian; Niebauer, Michael; Römling, Lukas; Pham, Adrian; Kolesnik-Gray, Maria; Evanschitzky, Peter; Vogel, Nicolas; Krstic, Vojislav; Rommel, Mathias; Hutzler, Andreas (Advanced Optical Materials, 2024)
Van der Waals materials and devices incorporating them exhibit highly thickness-dependent properties. The small lateral dimensions of mechanically exfoliated 2D-layered flakes, however, remarkably complicate their precise thickness determination. Quantitative analysis of reflectance measurements using optical microspectroscopy is proven to be as precise as spectroscopic ellipsometry while providing an easily adaptable and non-destructive method for thickness determination. The use of magnifying objective lenses allows obtaining the reflectance within a measurement spot of only a few microns in diameter. When the dimensions of exfoliated flakes are even smaller, however, the acquired reflectance is a superposition of those of the material of interest and the subjacent materials. To overcome this limitation, a facile approach to reduce the resolvable structure size by combining the evaluation of the reflectance measurement via transfer matrix method with spatial information extracted from optical micrographs is introduced. The efficacy when characterizing micrometer-sized flakes is exemplarily demonstrated for thickness determination of highly oriented pyrolytic graphite and a thin film of silicon dioxide. It is shown that a maximum error of less than 10% is achieved even when the flake only covers 20% of the measurement spot.
CRIS-Team Scopus Importer:2025-02-04
Keywords: 2D materials; graphite; reflectance; thin films; transfer matrix method